Jacinto Verdaguer poem - Verdaguer, Jacinto, 1845-1902.
Facsimile (1 volume, 33 pages) of an autograph version of Verdaguer's epic poem, L'Atlàntida.
Catalan poet.
Collection material in Catalan.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Catalan poetry; Poets